Comparative study of gravity effects in directional solidification of Al-3.5 wt.% Si and Al-10 wt.% Cu alloys - Guiyuan Zhang; Xinghong Luo; Yang Li; Shi Liu (npj Microgravity)
Abstract Directional solidification experiments of Al-3.5 wt.% Si and Al-10 wt.% Cu alloys were conducted under gravity and microgravity conditions using a 50-m-high drop tube. The solidification morphology of the two alloys is mainly columnar dendrites and equiaxed dendrites, respectively. The dendrite arm spacing (DAS), eutectic content, grain size, and compositional distribution of both alloys exhibit distinct characteristics under gravity and microgravity conditions. The study introduces an innovative perspective by taking solute density and its redistribution behavior into account when discussing the gravity effects during the directional solidification of alloys. The results indicate that the way gravity works on the solidification behavior of alloys depends strongly on the redistribution behavior and density of solute as well as crystallization modes, such as columnar grain or equiaxed grain. These findings are helpful in clarifying the coupling mechanism of gravity and relevant factors on the solidification of alloys, not only contributing to understanding the effect of gravity on solidification better but also offering valuable guidance for eliminating solidification segregation and producing high-performance alloys.